Perspectives of Peruvian professionals on declarations of advance directives - Enriquez Canto, Yordanis (2021)
To examine the opinions and perspectives of Peruvian doctors, lawyers, and notaries on advance directives, based on familiarity with Law 29633, a qualitative study was carried out. Semi-structured interviews were conducted with 15 professionals following an open approach with subsequent thematic analysis according to Braun and Clarke. Most respondents were male. The ages ranged from 35 to 60 years, with work experience of 10 to 30 years. Three main themes were identified: respect for the person's autonomy through a declaration of advance directive will be executed by a close relative; the scope of the manifestation of the advance directive be formalized in a public instrument; respect for one's own will and the will of others, with nine sub-themes. Understanding the perspective of doctors and lawyers is a support for the discussion of advance directives by helping to close the legal and ethical gaps.